Development of English Teaching Media Using Macromedia Flash 8 to Improve Students' Learning Motivation - Sumirah; Surayya, Ely; Khuliyatun, Siti (Yayasan Literasi Kita Indonesia, 2024)
This study aims to develop a learning media with the Macromedia Flash 8 application to increase the learning motivation of class X MA PKP Al-Hidayah Jambi City. The researcher chose the Macomedia Flash 8 application because it makes it possible to create interactive learning media which consists of complete features so that the developed media is able to actively involve students' senses of sight and hearing so that the material absorption process becomes more optimal. And in the end the learning objectives can be achieved. This study aims to develop a learning media with the Macromedia Flash 8 application to increase the learning motivation of class X MA PKP Al-Hidayah Jambi City. The researcher chose the Macomedia Flash 8 application because it makes it possible to create interactive learning media which consists of complete features so that the developed media is able to actively involve students' senses of sight and hearing so that the material absorption process becomes more optimal. And in the end the learning objectives can be achieved. The results of this study are English teaching media in terms of validity, display quality, presentation quality and attractiveness aspects. Based on the results of the assessment questionnaire, media expert lecturers, design experts, and material experts gave the results of the assessment questionnaire in the very good category. The results show that aspects of convenience, attractiveness, efficiency and effectiveness of the product have been achieved. This proves that this product fits the needs and increases student motivation. Based on this research, learning subjects using macromedia flash 8 teaching media is in accordance with the needs of class X MA PKP Al-Hidayah Jambi City students. The development of this product can increase students' learning motivation.